THE MEXICAN FRANKLINIELLA FUSCA (HINDS), F. PALLIDA (UZEL) AND F. SCHULTZEI (TRYBOM) SPECIES ASSEMBLAGES, IN THE "INTONSA GROUP" (INSECTA, THYSANOPTERA: THRIPIDAE) - Johansen, Roberto M. (Instituto de Ecología, A.C., 2002)
The species Frankliniella fusca (Hinds) is reviewed for Mexico, together with the description of two related also Mexican new species, all integrated in a species assemblage. Frankliniella pallida (Uzel) from Europe, is also reviewed, together with the description of three related Mexican new species, all forming a species assemblage. Frankliniella hemerocallis J.C.Crawford, Frankliniella schultzei (Trybom) and a New Mexican species, are also considered as a species assemblage. The adults of the three specific assemblages studied herein, lack a posteromarginal comb in tergite VIII. In the case of the F. fusca, F. pallida and F. schultzei species assemblages, the morphologic and color characters are discussed, as well as their probable relationships with other assemblages within the "Intonsa Group". Illustrations of the head, antennae, thorax and abdomen of each species, are included.